Characteristics and Outcomes of Intravenous Thrombolysis in Mild Ischemic Stroke Patients - Tang, Huan; Yan, Shenqiang; Wu, Chenglong; Zhang, Yanxing (Frontiers in Neurology, 2021)
Objective: This study assessed the characteristics of intravenous thrombolysis (IVT) with respect to early neurological deterioration (END) and functional outcome in mild ischemic stroke patients. Methods: Data were obtained from acute mild ischemic stroke patients (defined as having a National Institute of Health Stroke Score (NIHSS) ≤ 5) treated with IVT in our hospital from July 2017 to December 2020. END was defined as the NIHSS increased ≥1 over the baseline at 24 h after IVT. A modified Rankin scale (mRS) ≤ 1 at 3 months was considered as a favorable outcome, and an mRS ≥2 at 3 months was an unfavorable outcome. Results: Two hundred thirty-three acute mild ischemic stroke patients (all patients underwent MRI and DWI restriction) with IVT were included in this study. Thirty-one patients experienced END, and 57 patients experienced an unfavorable outcome at 3 months. With multivariate analysis, END was associated with an elevated baseline systolic blood pressure (SBP) (OR = 1.324, 95% CI, 1.053–1.664, p = 0.016) and coronary heart disease (OR = 4.933, 95% CI, 1.249–19.482, p = 0.023). An unfavorable outcome at 3 months after IVT was independently associated with a baseline elevated SBP (OR = 1.213, 95% CI, 1.005–1.465, p = 0.045), baseline NIHSS (OR = 1.515, 95% CI, 1.186–1.935, p = 0.001), prior hyperlipemia (OR = 3.065, 95% CI, 1.107–8.482, p = 0.031), cardioembolic stroke (OR = 0.323, 95% CI, 0.120–0.871, p = 0.025), and END at 24 h (OR = 4.531, 95% CI, 1.950–10.533, p < 0.001) in mild ischemic stroke patients. Conclusion: In mild ischemic stroke patients with IVT, an elevated baseline SBP and coronary heart disease were associated with END. The elevated baseline SBP, baseline NIHSS, a history of prior hyperlipemia, cardioembolic stroke, and END at 24 h after IVT were useful in predicting an unfavorable outcome at 3 months.